Peran Sustainability Reporting Disclosure dalam Memediasi Pengaruh Good Corporate Governance dan Leverage terhadap Kinerja Keuangan pada Emiten Energi Terbarukan di BEI Tahun 2022–2024 - Della Widyasari; Cholis Hidayati (Journal of Economics, Management, and Accounting, 2026)
This study analyzes the role of Sustainability Reporting Disclosure (SRD) in mediating the influence of Good Corporate Governance (GCG) and leverage on the financial performance of renewable energy companies listed on the Indonesia Stock Exchange during 2022–2024. The research employed a quantitative approach using secondary data collected from annual reports and sustainability reports, while purposive sampling was used to select the research sample. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that GCG has a positive and significant effect on SRD, but does not significantly affect financial performance. Leverage shows a positive and significant influence on financial performance, whereas SRD does not significantly affect financial performance and fails to mediate the relationship between GCG, leverage, and financial performance. These findings suggest that sustainability disclosure practices in renewable energy companies remain oriented toward compliance rather than serving as a strategic instrument for long-term financial value creation.